2020
DOI: 10.3390/f11020148
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of Pinus koraiensis in China: Current Situation and Future Prospects

Abstract: Pinus koraiensis (Sieb.et Zucc) is an economically and ecologically important tree species, naturally distributed in northeastern China. Conservation efforts and genetic improvement for this species began in the 1960s and 1980s, with the establishment of several primary seed orchards based on range-wide provenance evaluations. The original breeding objective was to improve growth and wood yield, but during the recent decade, it was redefined to include other traits, such as an enhancement of wood properties, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…Therefore, to protect and utilize precious wild resources of P. koraiensis, it is essential to evaluate the genetic diversity and genetic structure of natural germplasm resources, which provide useful genetic information for the protection of elite wild resources and for further research on the origin and evolution of this coniferous species and its related species. However, due to a lack of genome information, only a limited number of polymorphic molecular markers, such as simple sequence repeats (SSRs), have been developed and used in population genetics studies, which has greatly hindered the application of molecular marker technology in the study of genetic improvement of P. koraiensis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to protect and utilize precious wild resources of P. koraiensis, it is essential to evaluate the genetic diversity and genetic structure of natural germplasm resources, which provide useful genetic information for the protection of elite wild resources and for further research on the origin and evolution of this coniferous species and its related species. However, due to a lack of genome information, only a limited number of polymorphic molecular markers, such as simple sequence repeats (SSRs), have been developed and used in population genetics studies, which has greatly hindered the application of molecular marker technology in the study of genetic improvement of P. koraiensis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…They are the largest and most important species of gymnosperms with high economic and ecological values, which have a potential life span of 1000 years under natural growth conditions [1]. Conifers include about 613 species, mainly in the Pinaceae, Taxodiaceae and Cupressaceae families that are widely distributed over the world [2,3]. They appeared on earth's surface about three hundred million years ago [4].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of Korean pine dates back more than a half century [7]. To date, significant gains have been realized, and several studies reported some improvements in growth rate, and seed and wood quality [8][9][10][11]. Facing multiple needs and a permanent global change, multi-objective approaches have been suggested for the sustainable management of forest resources [12].…”
Section: Introductionmentioning
confidence: 99%